Prediction of an increase in oxygen requirement of SARS-CoV-2 pneumonia using three different scoring systems. Issue 2 (February 2021) - Kodama, Tatsuya; Obinata, Hirofumi; Mori, Hitoshi; Murakami, Wakana; Suyama, Yohsuke; Sasaki, Hisashi; Kouzaki, Yuji; Kawano, Shuichi; Kawana, Akihiko; Mimura, Satoshi
Abstract: Introduction: In patients with severe coronavirus disease 2019 (COVID-19), respiratory failure is a major complication and its symptoms occur around one week after onset. The CURB-65, A-DROP and expanded CURB-65 tools are known to predict the risk of mortality in patients with community-acquired pneumonia. In this retrospective single-center retrospective study, we aimed to assess the correlations of the A-DROP, CURB-65, and expanded CURB-65 scores on admission with an increase in oxygen requirement in patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pneumonia. Methods: We retrospectively analyzed 207 patients who were hospitalized with SARS-CoV-2 pneumonia at the Self-Defense Forces Central Hospital in Tokyo, Japan. Performance of A-DROP, CURB-65, and the expanded CURB-65 scores were validated. In addition, we assessed whether there were any associations between an increase in oxygen requirement and known risk factors for critical illness in COVID-19, including elevation of liver enzymes and C-reactive protein (CRP), lymphocytopenia, high D-dimer levels and the chest computed tomography (CT) score. Results: The areas under the curve for the ability of CURB-65, A-DROP, and the expanded CURB-65 scores to predict an increase in oxygen requirement were 0.6961, 0.6980 and 0.8327, respectively, and the differences between the three groups were statistically significant (p < 0.001). Comorbid cardiovascular disease, lymphocytopenia, elevated CRP, liver enzyme and D-dimer levels, and higher chest CT score were significantly associated with an increase in oxygen requirement Conclusions: The expanded CURB-65 score can be a better predictor of an increase in oxygen requirement in patients with SARS-CoV-2 pneumonia.